(untitled) (American Journal of Islam and Society, 2006)
This remarkable collaboration of primarily Maria Jaschok and Shui Jingjun (with contributions from nine other mostly Muslim Chinese women who are duly acknowledged), contains a wealth of information on a subject that most scholars of Muslim communities have never considered or perhaps even imagined: the existence of bona fide women’s mosques in China. Through painstaking historical, archival, interview, and field research, the authors lay out a convincing argument that such mosques have existed in China and continue to experience a “rapid increase” (p. 15), at least since the late Ming dynasty (sixteenth to seventeenth centuries), proliferating in northern China’s central plains region (mainly Henan, Hebei, Shandong, and Anhui) during the Qing emperor Jiaqing’s reign (1796-1820) (pp. 67-69). This work sheds light on “how women [in China] engendered and sustained faith, aspiration and loyalties under often challenging conditions” (p. 5) – which is putting it mildly. Strenuously caught between Confucian, Islamic, and patrimonial requirements, they developed an institution of learning and cultural transmission perhaps unique to the Muslim world. While the authors never fully address why “women’s mosques” and madrassahs developed so fully in China (and almost nowhere else), they do richly demonstrate the extraordinarily important role these religious and educational centers have played in preserving and promoting Islamic understanding among China’s Muslims, known as the Hui national minority (with a year 2000 population of approximately 9.8 million, out of a total 20.3 million Muslims in China, according to the especially accurate PRC state census). While the authors claim these women’s “prayer halls” (the Chinese term is ambiguous) and the women who lead them are fully-fledged ahongs or imams (again, the Chinese term, like the Arabic and Persian equivalents, is not clear about the teacher’s actual status), the issue here is whether they have any authority over men. Since they clearly do not, ahong should be taken in its more general sense of “one possessing advanced Islamic knowledge” or training, and does not imply institutionalized authority beyond the sphere of women (and children, which in most instances includes boys). Nevertheless, it is significant that they have such organized authority, training, and separate prayer halls or mosques among themselves ...